Symptom flares in women with chronic pelvic pain: questionnaire study within a cohort study (translational research in pelvic pain (TRiPP)) - Coxon, L; Lugt, C; Horne, AW; Evans, E; Abreu- Mendes, P; Arendt-Nielsen, L; Aziz, Q; Becker, CM; Birch, J; Charrua, A; Demetriou, L; Ferreira-Gomes, J; et al. (Wiley, 2024)
Objective: To quantify the variation, triggers and impact on quality of life of symptom flares in women with chronic pelvic pain (CPP). Design: Cross-sectional questionnaire within the Translational Research in Pelvic Pain clinical cohort study. Setting: Women with CPP, with subgroups of women with endometriosis (EAP), interstitial cystitis/bladder pain syndrome (BPS), comorbid endometriosis and interstitial cystitis/bladder pain syndrome (EABP), and those with pelvic pain without endometriosis or interstitial cystitis/bladder pain syndrome (PP). Population or Sample: A total of 100 participants. Methods: Descriptive and comparative analysis from flares questionnaire. Main Outcome Measures: The prevalence, characteristics and triggers of short, medium and long symptom flares in CPP. Results: We received 100 responses of 104 questionnaires sent. Seventy-six per cent of women with CPP have ever experienced symptom flares of at least one length (short, medium and/or long). Flares are associated with painful and non-painful symptoms. There is large variation for the frequency, duration, symptoms and triggers for flares. Over 60% of participants reported flares as stopping them from doing things they would usually do, less than 80% reported thinking about symptoms of flares and less than 80% reported flares being bothersome. Conclusions: Flares are prevalent and clinically very important in CPP. More research is needed to elucidate the mechanisms and characteristics underlying flares. Clinical practice should include an enquiry into flares with the aim of finding strategies to lessen their burden.